Morphometric study of distance between posterior inferior iliac spine and ischial spine of the human hip bone for sex determination - Sinha, Abhishek Prasad; Kumari, Anamika; Ali, Sadakat; Jethani, S. L. (International Journal of Research in Medical Sciences, 2017)
Background: Objective of current study was to study the distance between Posterior Inferior Iliac Spine and Ischial Spine (PIIS-IS) of human hip bone for determination of sex. Methods:The study comprised unpaired 149 adult human hip bones of known sex. The posterior inferior iliac spine and ischial spine were identified in all the hip bones and a vernier calliper was used to measure the distance between the PIIS-IS. Results:It was observed that the mean distance of PIIS-IS in males and females were 49.64 mm and 54.35 mm respectively. The standard deviation in males was 5.75 mm and that of females was 5.15 mm. Maximum no. i.e. 78.66% of males & 62.16% comes under the range of distance between 41-55 mm. Conclusion:It was observed that out of 149 hip bones taken for study 75 were of males and 74 were of females. The Mean distance in females was observed to be greater in comparison to males. Statistically calculated T- test reveals that the parameter taken for study is very highly significant in terms of sex differentiation.